Empowering the Tracking Performance of LEO-Based Positioning by Means of Meta-Signals - Nardin, Andrea; Dovis, Fabio; Fraire, Juan A. (IEEE journal of radio frequency identification (Online), 2021)
Global Navigation Satellite Systems (GNSSs) are the most widespread technology for Position Navigation and Timing (PNT). They have been traditionally deployed exploiting Medium Earth Orbit (MEO) or Geosynchronous Orbit (GSO) satellites. To meet future demands and overcome MEO and GSO limitations, GNSSs based on Low Earth Orbit (LEO) constellations have been investigated as a radical system change. Although characterized by a higher Doppler effect, a PNT service supplied by LEO satellites can provide received signals that are about 30 dB stronger. Moreover, broadband LEO constellations and the forthcoming mega-constellations can be exploited to deliver a piggybacked PNT service. With this cost-effective solution, a PNT service might be subject to substantial bandwidth limitations. A narrowband implementation of the so-called meta-signal approach in GNSS receivers, namely Virtual Wideband (VWB), can tolerate harsh Doppler conditions while reducing the processed bandwidth. It is thus suited to a secondary PNT service delivered by LEO satellites. The aim of this work is to show the applicability of the VWB architecture to signals provided by a piggybacked PNT service, hosted on a mega-constellation. Through this case study we demonstrate the capability of this implementation to bear high Doppler conditions while empowering the potential of LEO PNT.